Metaphors, materialities, and affordances: Hybrid morphologies in the design of interactive artifacts. (November 2017) - Jung, Heekyoung; Wiltse, Heather; Wiberg, Mikael; Stolterman, Erik
Abstract : As materiality of interactive artifacts is diversified with integrated physical and digital materials, metaphoric design approaches in Human–Computer Interaction (HCI) go beyond resembling the appearance of physical objects, exploring novel materials and forms of interactive artifacts. The hybrid materialities and forms of artifacts influence how interactivity is perceived, reframing the concept of affordances according to its evolving relationship to metaphors and materialities. By conceptualizing interactive forms in their surface, behavioral and systemic aspects, we examine multifaceted roles of metaphors in HCI from concealing and revealing a formal system to expanding and reifying its meaning; and propose a morphologic perspective on affordances as an invitation for making variations of interactive forms by compositing multiple design resources. Highlights: The form of interactive artifacts consists of their surface, behavior and system. Material and computational properties of digital media shape design affordances. Design conventions in formal compositions influence on interaction affordances. Metaphors remediate design conventions across different material domains of media. Metaphors can be used to explore materialities and affordances of digital media.